RANCANG BANGUN KUSTOMISASI MODEL KARAKTER 3D DENGAN TEKNIK CUT OUT MENGGUNAKAN PHYTONSCRIPT - Nugroho, Agus; Suyanto, M.; Sofyan, Amir Fatah (Universitas Respati Yogyakarta, 2013)
Production stage has a lot of processes through which to produce an animated film. 3D modeling process to cut out requires design techniques that are shared with some of some processes like image painting, modeling and rigging for its formation. Modeling object plane is a flat shape that can be used for the manufacture of cut out animation characters in 3D workmanship. All flat objects are organized in such a way that it looks like a character. Character modeling process is a key element of the animation production workflow that usually takes the longest of the various stages of the production process, it requires a new method to speed up the process modeling phase of the character. Python script in Blender software can be used to assist the process of modeling the production phase. So with character customization methods generated by Python scripts, modeling process will be accelerated and facilitated to generate more than one character to customize the character models already exist, so will summarize the workflow in the production phase.Â Keywords: Cut out, Modelling, Pythonscript, 3D